Recent progress on synthesis of ZIF-67-based materials and their application to heterogeneous catalysis - Duan, Chongxiong; Yu, Yi; Hu, Han (Green energy & environment, 2022)
In recent years, an increasing amount of interest has been dedicated to the synthesis and application of ZIF-67-based materials due to their exceptionally high surface area, tunable porosity, and excellent thermal and chemical stabilities. This review summarizes the latest strategies of synthesizing ZIF-67-based materials by exploring the prominent examples. Then, the recent progress in the applications of ZIF-67-based materials in heterogeneous catalysis, including catalysis of the redox reactions, addition reactions, esterification reactions, Knoevenagel condensations, and hydrogenation–dehydrogenation reactions, has been elaborately discussed. Finally, we end this work by shedding some light on the large-scale industrial production of ZIF-67-based materials and their applications in the future. In this review, we discuss various strategies for the preparation of ZIF-67-based materials including the solvothermal method, surfactant-assisted method, sol–gel method, and microwave/ultrasound-assisted method. We also discuss the applications of ZIF-67-based materials in heterogeneous catalysis fields including the redox reactions, addition reactions, esterifications, Knoevenagel condensations, and hydrogenation–dehydrogenation reactions. [Display omitted]